Creativity is always a social process - Elisondo, Romina Cecilia (2016)
The article explores the social essence of creativity. Two studies where interactions with others shape the development of creative processes are presented; first, theoretical perspectives on creativity as social process are discussed. The first study analyzes social aspects of creative processes developed during leisure activities. Men and women (N=150) living in Córdoba (Argentina) were interviewed in the research. The second study is a form of biographical research. The sample includes 22 Argentine personalities prominent in the scientific and artistic fields. As a main result, in the two studies we observed that links with family, teachers, peers, colleagues, mentors, tutors anddisciples shape the possibilities of developing everyday creativity as well as Big-C creativity. Finally, considerations and suggestions for future research on creativity as a social process are presented. Creativity emerges from dialogues, interactions and practices with others. It is not a solitary process: it involves languages, knowledge and actions that are socially constructed.